2019
DOI: 10.1108/imr-08-2016-0165
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamism in country of origin effect

Abstract: Purpose The purpose of this paper is to enrich country of origin (COO) effect in international marketing theory by adding the understanding of temporal dynamism into COO research. Design/methodology/approach Utilizing a qualitative and interdisciplinary phenomenological approach, this paper analyses historical and contemporary sources triangulated with contemporary primary interview data. The example of how perceptions of Italians about the values typical of the British Sixties varied over time periods is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
4
0
1
Order By: Relevance
“…Semaan et al (2019) attempts to address such mixed results observed over time and within literature regarding the effectiveness and influence of the COO label, suggesting that the heuristic has different effects on different consumers in different temporal or evaluative contexts. The perception of a product's COO is malleable, with the appeal able to change over time because of evolving historical and contemporary beliefs and events (Amatulli et al, 2019). For example and regarding British branding reputation, the 2001 foot and mouth disease crisis within Britain not only instigated a change in consumer behaviour towards British meat produce, but also generated a debate over local vs. commercial purchasing (Hartnett et al, 2007).…”
Section: The Coo Effectmentioning
confidence: 99%
See 3 more Smart Citations
“…Semaan et al (2019) attempts to address such mixed results observed over time and within literature regarding the effectiveness and influence of the COO label, suggesting that the heuristic has different effects on different consumers in different temporal or evaluative contexts. The perception of a product's COO is malleable, with the appeal able to change over time because of evolving historical and contemporary beliefs and events (Amatulli et al, 2019). For example and regarding British branding reputation, the 2001 foot and mouth disease crisis within Britain not only instigated a change in consumer behaviour towards British meat produce, but also generated a debate over local vs. commercial purchasing (Hartnett et al, 2007).…”
Section: The Coo Effectmentioning
confidence: 99%
“…Ultimately however, it appears that such labelling practice is a key driver for consumers within their purchasing decisions for FMCGs, but different and underlying socio-political, socio-economic and other psychological concepts or cues may interact with its influence or attribute associations (Amatulli et al, 2019). Research has begun to support the idea that the label's effectiveness not only varies across different product categories and consumer groupings, but that its influence also varies across temporal and spatial dimensions in response to changing external conditions.…”
Section: Common Coo Communication Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Negli Stati Uniti e nel Regno Unito questi studi a livello accademico sono appannaggio soprattutto di esperti della comunicazione. In Italia, nonostante un ritardo radicato nell'accoglienza e nella comprensione della musica pop anglosassone (Amatulli et al 2019), si stanno muovendo passi significativi in ambito sociologico (Tosoni e Zuccalà 2013) e storico anche grazie a Moicana. Centro studi sulle controculture (Moicana 2018).…”
Section: Musica E Identità: Una Fonte Per Leggere La Gioventù Del Novecentounclassified